PENGEMBANGAN MEDIA PAPALA (PAPAN PANCASILA LIMA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SDN TERJAN REMBANG - Ihda Lailatul Fajriyah; Iis Daniati Fatimah (Prodi PGSD Universitas PGRI Ronggolawe, 2023)
PPKn is a subject that is used as a vehicle for preserving the noble values ​​of the nation's culture. But in fact the ability to master material in Civics subjects, especially material for practicing the Pancasila precepts, is still relatively low. Therefore, creative and innovative teaching materials are needed. This study aims to develop and produce PAPALA Media (Papan Pancasila Lima) that meet valid, effective, and practical criteria. This type of research is research and development (Research and Development) with the ADDIE model (Analysis, Design, Develop, Implement, Evaluate). The subjects of this research were grade II elementary school students. Data collection instruments were interviews, validation sheets, student and teacher response questionnaires, and student test sheets. The data obtained were then analyzed using qualitative data analysis techniques and quantitative data analysis techniques. The results of this study are that the product developed at the material validation stage gets a result of 75% and is declared valid. Language validation gets a percentage of 80% and is declared valid. Media validation obtained a percentage of 84% and was declared very valid. The results of the practicality test from the user (teacher) get a percentage of 95.55% and are declared very practical and the practicality test of students get a score of 94.71% and are declared very practical. While the results of the effectiveness test from PAPALA (Papan Pancasila Lima) got 84.28% and were declared very effective.